First record of molluscs naturally infected with Angiostrongylus cantonensis (Chen, 1935) (Nematoda: Metastrongylidae) in Brazil - Caldeira, Roberta Lima; Mendonça, Cristiane LGF; Goveia, Christiane Oliveira; Lenzi, Henrique L; Graeff-Teixeira, Carlos; Lima, Walter S; Mota, Ester M; Pecora, Iracy Lea [UNESP]; Medeiros, Aline Maria Zigiotto de [UNESP]; Carvalho, Omar dos Santos (Instituto Oswaldo Cruz, Ministério da Saúde, 2007)
Seeking the identification of Angiostrongylus cantonensis as a potential etiological agent of three clinical cases of eosinophilic meningitis, mollusc specimens were collected in the state of Espírito Santo, Brazil. The snails were identified as Sarasinula marginata (45 specimens), Subulina octona (157), Achatina fulica (45) and Bradybaena similaris (23). Larvae obtained were submitted to polymerase chain reaction and restriction fragment length polymorphism diagnosis. Their genetic profile were corresponded to A. cantonensis. Rattus norvegicus experimentally infected with third-stage larvae, developed menigoencephalitis, and parasites became sexually mature in the lungs. Additionally, larvae obtained from A. fulica snails, from São Vicente, state of São Paulo, also showed genetic profiles of this nematode. This is the first record of Brazilian molluscs infected with this nematode species.
Keywords: Angiostrongylus cantonensis; terrestrial molluscs; Brazil